2020
DOI: 10.1111/tme.12704
|View full text |Cite
|
Sign up to set email alerts
|

Skin flora and bacterial contamination of diversion pouch and recovered platelet components in Moroccan blood donors

Abstract: Objective: The objective of this study was to evaluate bacterial reduction procedures used during whole-blood donations in Morocco. Background: Bacterial contamination still poses serious challenges to blood safety, especially in countries with limited resources. Methods: In the first part of this study, we analysed 233 swab samples taken from blood donors' antecubital fossa. After donation, a second batch of samples was analysed from the diversion pouches of corresponding donors. In addition, we searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Con respecto a la ubicación precisa de los microorganismos dentro de la sangre humana, la literatura más reciente sugiere que los taxones bacterianos pueden sobrevivir dentro de los hematíes, plaquetas y linfocitos con un 93,74 % del ADN bacteriano integrado 5,17,18 . Ejemplos de bacterias intracelulares son la Chlamydia pneumoniae (causante de la neumonía), habita en células mononucleares de sangre periférica en individuos sanos 19 .…”
Section: Resultados Y Discusiónunclassified
“…Con respecto a la ubicación precisa de los microorganismos dentro de la sangre humana, la literatura más reciente sugiere que los taxones bacterianos pueden sobrevivir dentro de los hematíes, plaquetas y linfocitos con un 93,74 % del ADN bacteriano integrado 5,17,18 . Ejemplos de bacterias intracelulares son la Chlamydia pneumoniae (causante de la neumonía), habita en células mononucleares de sangre periférica en individuos sanos 19 .…”
Section: Resultados Y Discusiónunclassified
“…Studies in Finland, Tanzania, and Morocco showed frequencies of S. aureus and Gramnegative bacteria between 7%-16.74% and 13.73%-41.2% of blood donors, respectively. 8,19,20 Of note, the Tanzanian study sampled skin from healthy participants (no blood donors) at the sterno-clavicular joint, which is categorized as sebaceous and a typical habitat for Gram-positive skin bacteria, whereas the antecubital fossa is categorized as moist and harbors Gram-negative bacteria. 16 In the Moroccan study, participants were voluntary blood donors, onethird of them trainees at the study hospital.…”
Section: Discussionmentioning
confidence: 99%
“…), but also Pantoea spp., Enterobacter spp., Roseomonas mucosa, and Moraxella osloensis have previously been isolated from healthy skin. 10,17,19,20 Worldwide, sSA has the highest death rate attributable to antimicrobial resistance, and multidrug resistance is common in hospitals 22,23 : the fact that only a few of the Gram-negative isolates displayed multidrug antibiotic resistance may indicate their community rather than hospital origin. Among Staphylococcus aureus, two isolates were MRSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation